Pengaruh Layanan Bimbingan Kelompok dengan Permainan Kartu Karir Terhadap Sikap Pilihan Karir - Priambodo, Agus (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
This research aims to find out whether the guidance group with a media career card game can have an effect on the attitudes of students career choice. This type of research uses experimental research design research with one group pre test and post test. The population in this research is the grade IX E SMP N 1 Ungaran which amounted to 35 students. The sampling technique using a purposive sampling, with a sample of 10 students. Data collection tools using interviews and career options attitude scale. Analytical techniques descriptive data using the wilcoxon test and the percentage of pairs match. Research results show that the attitude of students career choice before and after given the guidance group with media card game career experienced an increase of 11,82%. It indicates that the guidance group with a media career card game media effect on the attitude of students career choices.